Funkcjonalna specyfika typów somatycznych u dzieci - Welon, Zygmunt (Polskie Towarzystwo Antropologiczne, 1986)
The problem was analysed on the basis of examinations carried out in 1334 children in the age of 9 years from Lower Silesia. Anthropometric measurements by the modified Parnell’s method served to determine the somatotypes of the children. A battery of 6 tests of motoric fitness was used as the functional characteristics of the distinguished somatotype groups: L, M, T and S. During the analysis very distinct differences in the motoric fitness were found between the distinguished somatotype groups mainly due to the elimination of disturbing factors, differences in body height and in the level of developmental progress of children in the groups: L, M, T and S. The obtained results supply another successive proof of the reality of constitutional types in children, and we can already determine these types by a set of morpho-functional traits.
Functional specificity of somatotypes in children